Return to play following spine surgery - Tetreault, Tyler A.; Garg, Sumeet (Frontiers in Pediatrics, 2023)
Return to physical activity is a primary concern for adolescents with idiopathic scoliosis indicated for spinal fusion surgery. Preoperative counseling often addresses concerns regarding ability to return to sport, postoperative restrictions, time away from play, and safety of returning to activities. Previous works have shown that flexibility can noticeably decrease after surgery, and that ability to return to the same level of play may be impacted by the levels of the spinal column included in the spinal fusion. Equipoise remains on when patients should be allowed to return to non-contact, contact, and collision sports activities; however, there is a trend toward earlier release to activities over the last few decades. Sources agree, though, that return to sport is safe, with rare instances of complications reported for patients with spinal fusion.